Prognostic Importance of Diastolic Dysfunction in Relation to Post Procedural Aortic Insufficiency in Patients Undergoing Transcatheter Aortic Valve Replacement. Issue 3 (24th May 2016) - Kampaktsis, Polydoros N.; Bang, Casper N.; Chiu Wong, S.; Skubas, Nikolaos J.; Singh, Harsimran; Voudris, Konstantinos; Baduashvili, Amiran; Pastella, Kalliopi; Swaminathan, Rajesh V.; Kaple, Ryan K.; Minutello, Robert M.; Feldman, Dmitriy N.; et al.
Abstract : Objectives: We sought to examine whether baseline diastolic dysfunction (DD) is associated with increased mortality in patients who develop aortic insufficiency (AI) after transcatheter aortic valve replacement (TAVR). Background: Significant post‐TAVR AI is associated with increased mortality, likely secondary to adverse hemodynamics secondary to volume overload and decreased LV compliance from chronic pressure overload. However, the effect of baseline DD on outcomes of patients with post‐TAVR AI has not been studied. Methods: A total of 195 patients undergoing TAVR were included in the study. Patients with moderate‐to‐severe mitral stenosis, prior mitral valve replacement or atrial fibrillation were excluded. DD was classified at baseline by a 2‐step approach as recommended by the American Society of Echocardiography while AI was evaluated 30 days post‐TAVR. Follow up data up to 2 years post‐TAVR was used in survival analysis. Results: Patients with severe baseline DD who developed ≥mild post‐TAVR AI had increased mortality compared to all other patients (HR = 3.89, CI: 1.76–8.6, P = 0.001), which remained significant after adjusting for post‐TAVR AI, pre‐TAVR AI, baseline mitral regurgitation, ejection fraction, pulmonary artery pressure, creatinine clearance and history of stroke. Conclusions: Even mild post‐TAVR AI may have a negative impact on outcomes of patients with underlying severe DD. © 2016 Wiley Periodicals, Inc.